1995
DOI: 10.1128/jvi.69.2.955-967.1995
|View full text |Cite
|
Sign up to set email alerts
|

Induction of AIDS by simian immunodeficiency virus from an African green monkey: species-specific variation in pathogenicity correlates with the extent of in vivo replication

Abstract: Previous studies suggested that simian immunodeficiency viruses isolated from African green monkeys (SIVagm) are relatively nonpathogenic. The report describes the isolation and biologic and molecular characterization of a pathogenic SIVagm strain derived from a naturally infected African green monkey. This virus induced an AIDS-like syndrome characterized by early viremia, frequent thrombocytopenia, severe lymphoid depletion, opportunistic infections, meningoencephalitis, and death of five of eight macaques w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(86 citation statements)
references
References 35 publications
3
82
0
1
Order By: Relevance
“…Persistent infection and/or AIDS-like disease progression have also been observed in pig-tailed macaques inoculated with primary isolates of HIV-2 [37,43], in contrast to the common observation of transient infection and lack of pathogenicity in HIV-2 infected rhesus macaques [11,16]. Hirsch et al [26] passaged SIVagm in pig-tailed macaques and observed speciesspecific variations in pathogenicity correlating with the extent of in vivo replication. Chen et al [12] observed enhanced infectivity, but no pathogenicity, after serial passages of an R5-tropic subtype C SHIV in pig-tailed macaques.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent infection and/or AIDS-like disease progression have also been observed in pig-tailed macaques inoculated with primary isolates of HIV-2 [37,43], in contrast to the common observation of transient infection and lack of pathogenicity in HIV-2 infected rhesus macaques [11,16]. Hirsch et al [26] passaged SIVagm in pig-tailed macaques and observed speciesspecific variations in pathogenicity correlating with the extent of in vivo replication. Chen et al [12] observed enhanced infectivity, but no pathogenicity, after serial passages of an R5-tropic subtype C SHIV in pig-tailed macaques.…”
Section: Introductionmentioning
confidence: 99%
“…healthy carriers [19]. Among these other isolates only the SIV from African green monkeys has, thus far, proven experimentally pathogenic in macaques [23].…”
Section: Simian Immunodeficiency Virus (Siv)mentioning
confidence: 99%
“…At least 12 SIV strains induce AIDS (within one year) when cultured in adapted cell lines and transferred as tissue culture supernatant to simian species (largely Asian macaques). Here, AIDS is defined by the depletion of CD4Ă· T lymphocytes and several indicator opportunistic infections, namely, Pneumocystis caHnii pneumonia, Mycobacterium avium, oral candidiasis, meningoencephalitis, and lymphoma [80][81][82]. Two pathogenic SIV strains (SIVMACA239, SIVAGM90) have been molecularly cloned and the molecular clones have been used to induce AIDS in macaques [80][81][82].…”
Section: Simian Immunodeficiency Virus Causes Aids In Monkeysmentioning
confidence: 99%
“…Here, AIDS is defined by the depletion of CD4Ă· T lymphocytes and several indicator opportunistic infections, namely, Pneumocystis caHnii pneumonia, Mycobacterium avium, oral candidiasis, meningoencephalitis, and lymphoma [80][81][82]. Two pathogenic SIV strains (SIVMACA239, SIVAGM90) have been molecularly cloned and the molecular clones have been used to induce AIDS in macaques [80][81][82]. Control macaques inoculated with saline, with inactivated SIVMAcA239 or with SIVMACA239 carrying mutations/deletions in the nef gene failed to induce AIDS in the same macaque species [80,83,84].…”
Section: Simian Immunodeficiency Virus Causes Aids In Monkeysmentioning
confidence: 99%